2016
DOI: 10.1080/14767058.2016.1262342
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Uterine packing versus Foley’s catheter for the treatment of postpartum hemorrhage secondary to bleeding tendency in low-resource setting: A four-year observational study

Abstract: The use of uterine packing to arrest PPH is simple, quick and safe procedure to avoid further surgical interventions and to preserve the fertility in low-resource setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Application of intrauterine pressure to produce an internal compression effect to control PPH has probably evolved from uterine packing. While the earliest reports of uterine packing could be dated back to the 19th century, recent studies comparing uterine packing techniques with IUBT have found that they were equally effective without any increase in infective morbidity . In practice, effective uterine packing required appropriate training, and the packing procedure would likely take longer than the inflation of an IUBT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Application of intrauterine pressure to produce an internal compression effect to control PPH has probably evolved from uterine packing. While the earliest reports of uterine packing could be dated back to the 19th century, recent studies comparing uterine packing techniques with IUBT have found that they were equally effective without any increase in infective morbidity . In practice, effective uterine packing required appropriate training, and the packing procedure would likely take longer than the inflation of an IUBT.…”
Section: Discussionmentioning
confidence: 99%
“…Severe PPH was defined as an estimated blood loss exceeding 1000 mL. The procedure for the application of the Bakri balloon was in accordance with that generally described in the literature . The Bakri balloon can be placed transvaginally through the cervix or transabdominally through the caesarean uterine wound.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In my study, safety was significantly high in uterine packing group (Group A) compared to Foley's catheter balloon tamponade (group B) (72.34% versus 31.91%; respectively) with p-value of 0.0001 while comparing effectiveness, hemorrhage was controlled in 93.3% of uterovaginal packing cases compared to only 68.1% in the other group (p < 0.05). 13 In a study, Ashraf N and colleagues determined the efficacy of uterine packing for controlling PPH and they observed the success rate in 59.4% of patient while fever was noted in 92.5% of patient. 14 On the other hand, Ali MK et al found that Foley's catheter found effective in 88.2% of cases for controlling PPH while fever was noted in 26.7% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recently, Rezk M et al in their study found success of uterovaginal packing to be >90% while 69 % in the other group (p < 0.05). 13 In a study, Ashraf N and colleagues determined the efficacy of uterine packing for controlling PPH and they observed the success rate in 59.4% of patient while fever was noted in 92.5% of patient. 14 On the other hand, Ali MK et al found that Foley's catheter found effective in 88.2% of cases.…”
Section: Introductionmentioning
confidence: 99%